2020
DOI: 10.5539/elt.v13n2p16
|View full text |Cite
|
Sign up to set email alerts
|

Saudi EFL Learners’ Preferences of the Corrective Feedback on Written Assignment

Abstract: The aim of the current study is to investigate the Saudi English as a foreign language (EFL) learners’ preferences for corrective feedback on written assignments. This mixed-method study used a closed-ended Likert scale questionnaire that was adopted and adapted to suit the participants under investigation. Additionally, an open-ended question was used to gain more insight. Both instruments were completed by 114 Saudi female EFL learners whose ages ranged from 12 to 13 years old and who were studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
(43 reference statements)
3
16
0
Order By: Relevance
“…Additionally, the findings indicated that students preferred teacher feedback focusing on all aspects of writing, such as grammar, structure, meaning, spelling, and punctuation. Indeed, similar findings have been reported by several previous studies at the tertiary level (e.g., Alharbi, 2016;Alshahrani & Storch, 2014;Hamouda, 2011) and the intermediate school level (e.g., Qutob & Madini, 2020).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, the findings indicated that students preferred teacher feedback focusing on all aspects of writing, such as grammar, structure, meaning, spelling, and punctuation. Indeed, similar findings have been reported by several previous studies at the tertiary level (e.g., Alharbi, 2016;Alshahrani & Storch, 2014;Hamouda, 2011) and the intermediate school level (e.g., Qutob & Madini, 2020).…”
Section: Resultssupporting
confidence: 90%
“…assess the effectiveness of teacher feedback. Indeed, these studies generally relate to three main categories: studies investigating the effectiveness of teacher feedback (e.g., Biber, Nekrasova, & Horn, 2011;Ellis et al, 2008;Hubais & Dumaning, 2014;Rastgou, 2016;Wei & Cao, 2020), studies investigating the efficacy of different types of teacher feedback (e.g., Bitchener & Knoch, 2009;Chandler, 2003;Hosseiny, 2014;Storch & Wigglesworth, 2010), and studies exploring students' perceptions and attitudes towards teacher feedback (e.g., Al-Sawalha, 2016;Chen et al, 2016;Hamouda, 2011;Qutob & Madini, 2020;Zacharias, 2007). These studies generally reported that teacher feedback is useful and that students' value and use teachers' feedback.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Saudi context, many studies have investigated Saudi students' perceptions of different types of WCF (Aseeri, 2019;Hamouda, 2011;Mustafa, 2012;Qutob & Madini, 2020). A quantitative study was conducted by Aseeri (2019) to investigate Saudi teachers' and students' attitudes toward the most common techniques used in receiving feedback in L2 writing classrooms such as direct and indirect feedback.…”
Section: Studies Looking At Wcf In a Saudi Contextmentioning
confidence: 99%